Diverticulitis during pregnancy: A review of the reported cases - Kechagias, Konstantinos S.; Katsikas-Triantafyllidis, Konstantinos; Geropoulos, Georgios; Giannos, Panagiotis; Zafeiri, Marina; Tariq-Mian, Imran; Paraskevaidi, Maria; Mitra, Anita; Kyrgiou, Maria (Frontiers in Medicine, 2022)
Background Diverticular disease of the colon represents a common clinical condition in the western world. Its prevalence increases with age and only 5% of cases occur in adults younger than 40 years of age, making it a rare condition during pregnancy. The aim of this review was to provide an overview of the reported cases of diverticulitis during pregnancy. Methods We conducted a systematic review of the literature based on preferred reporting items for systematic review and meta-analysis (PRISMA) guidelines. We searched three different electronic databases namely PubMed, Scopus and Web of Science from inception to December 2021. Literature search and data extraction were completed in duplicates. Results The initial search yielded 564 articles from which 12 were finally included in our review. Ten articles were case reports and two were observational studies. The mean age of the cases was 34 years. The presenting complain was provided for 11 cases. The majority of the patients (10/11, 91%) presented with abdominal pain located mainly on the left (6/11, 55%) or right (4/11, 36%) iliac fossa. The most common diagnostic modality used for the diagnosis of the condition was ultrasonography in nine cases (9/12, 75%) followed by magnetic resonance imaging (MRI) in two cases (2/12, 17%). In spite of clinical and radiological evaluation, the initial diagnosis was inaccurate in seven cases (7/12, 58%). The therapeutic approach was available for 11 cases and it was based on the administration of intravenous antibiotics in six cases (6/11, 55%) and surgical management in five cases (5/11, 45%). Data for the type of delivery was provided in nine studies with five patients (5/9, 56%) delivering vaginally and four patients (4/9, 44%) delivering with cesarean section. Conclusion As advanced maternal age becomes more common, the frequency of diverticulitis in pregnancy may increase. Although available guidelines do not exist, the clinical awareness, early recognition of the disorder, using diagnostic modalities such as ultrasound and MRI, and rapid therapeutic approach with antibiotics, may improve maternal and neonatal outcomes.